Enhancement of anisotropic conductivity, elastic, and dielectric constants in a liquid crystal-gold nanorod system - Sridevi, S.; Prasad, S. Krishna; Nair, Geetha G.; D'Britto, Virginia; Bhagavatula L. V. Prasad (Applied Physics Letters, 2010)
We report electrical conductivity (sigma), dielectric constant (epsilon) and the elastic constant measurements in a nematic liquid crystal (LC) doped with small concentrations of gold nanorods. This LC-nanoparticle complex, shows not only orders of magnitude higher sigma, but also stabilizes its anisotropy. The epsilon data suggests an increased ordering in the nematic phase, and an improved antiparallel correlation of the molecules in the isotropic phase. Surprisingly, an anisotropic enhancement of the Frank elasticity is also seen. We suggest a possible electro/magnetomechanical conductivity switch and also provide explanations based on the aspect ratio of the nanoparticles vis-a-vis the LC molecules. (c) 2010 American Institute of Physics. [doi:10.1063/1.3499744]